Compact Integrated On-Chip MIMO Antenna with Reconfigurability for mmWave Frequencies - Khaled Boubekeur; Nicolas Zerounian; Badr Eddine Ratni (Sensors)
This paper presents a compact on-chip multiple-input multiple-output (MIMO) antenna designed for future communication systems, featuring frequency-agile elements. The antenna achieves enhanced decoupling and reduced cross-section through the integration of a metasurface, which also introduces frequency agility. Designed for the millimeter-wave band using low-loss BenzoCycloButene (BCB) polymer, the antenna is manufactured with microelectronic processes, and the dimensions are 7.54 × 7.54 × 0.055 mm3. Simulations and measurements demonstrate excellent frequency agility around 60 GHz, with gains of 6.5 to 9 dBi. As a proof of concept, open and short circuits were used for switching, with future designs aiming to incorporate diodes for a full dynamic reconfiguration. This work highlights the potential for compact, high-performance, and frequency-reconfigurable on-chip antennas in next-generation millimeter-wave systems.